PEMANFAATAN LIMBAH CAIR TAHU MENJADI BIOGAS SEBAGAI BAHAN BAKAR ALTERNATIF - Anis Maryati; Umi Octaviana; Widya Nur Anggraini (Universitas Sebelas Maret, 2014)
The tofu liquid waste has a high organic matter content and potential for biogas production as an alternative fuel source through anaerobic process . In general , biogas contains 50-80 % methane , CO2 , H2S and water . The treatment of tofu liquid waste into biogas is beneficial for the owner tofu factory not only contribute to protecting the environment but also increase revenue by reducing fuel consumption in the tofu production. The purpose of thr program to follow up of the PKM - M ( Student Creativity Program Society) to provide an introduction the treatment of tofu liquid waste into biogas as a fuel alternative and its application in the factory tofu owned by Mr. Jarwanto in Sumber Rejeki Village Rt 40 / Rw 7 Sidodadi District, Masaran Central Java . The methods of implementation through the simple design instrument with the principal part of digestive (digester) , raw material intake hole , out let of the products digestion sludge (slurry) , and the distribution pipes for biogas formed . In the tank digester is contain methane bacteria to decompose of organic matter and produce of biogas . The gas formed subsequently channeled into the pipes that are designed such that it can be directly utilized in such a way for example to the stove . The outcome this program to reduce the impact of environmental pollution as well as optimize the utilization of precisely and useful for the production of biogas that is easy and economical Keywords : tofu liquid waste , biogas , treatment , alternatif fuel